The forger's creed : reinventing art history in early modern China - Park, J. P. (University of California Press, 2025)
"In 1634, scholar-official Zhang Taijie (b. ca. 1588) published a book titled A Record of Treasured Paintings (C. Baohui lu), presenting an extensive catalog of a purportedly vast painting collection he claimed to have built. However, the entire book is Zhang's meticulously crafted forgery; he even forged paintings to match the documentation, and profited from trading them. Furthermore, the book intriguingly mirrors unfounded art-historical claims of its time. Prominent figures like Dong Qichang (1555-1636) made entirely fabricated arguments to assert legitimate lineages in Chinese art, designed to create a fictionalized history shaped by preferred beliefs rather than reality. While presenting the first comprehensive exploration of various forgery practices in early modern China-fabricated texts, forged paintings, and fictitious art history-The Forger's Creed examines the cultural, social, and genealogical desires, anxieties, and tensions prevalent in early modern China. Through thorough scrutiny of the historical irregularities introduced by these forgeries, J. P. Park highlights a peculiar and paradoxical phenomenon wherein forgeries transform into legitimate materials across Chinese history"--